Survey on Network Lifetime Enhancement Method - Jawad, Abdul; Mali, PB (International Journal of Computer Sciences and Engineering, 2025)
A vital challenge in the design of Wireless Sensor Network is to improve the network lifetime. Wireless Sensor nodes convey limited essential power source. In single static sink node based wireless sensor network, a sensor node spends the most of its energy for relaying data packets particularly which are situated in the surrounding area of the sink node. They distribute their energy so fast because of numerous to one traffic pattern and finally they die. This uneven depletion phenomenon is known as hot spot issue which gets to be more genuine as the number of sensor nodes increase. Replacing these energy sources in the field is normally not feasible. So if the distance between a sensor node and sink node is reduced which leads to decrease in energy utilization. This paper provides asurvey on various methods which are developed to increase the lifetime of a network. The sensor nodes close to the sink will generally consume more battery power than others; thus, these nodes will rapidly drain out their battery energy and shorten the network lifetime of the WSN. Sink relocation is an effective network lifetime augmentation technique, which avoids consuming an excess of battery energy for a particular gathering of sensor nodes. In this paper, propose a moving methodology called energy-aware sink relocation (EASR) for mobile sinks in WSNs. The proposed system utilizes data identified with the residual battery energy of sensor nodes to adaptively conform the transmission range of sensor nodes and the relocating scheme for the sink.